2017
DOI: 10.1016/j.ijsu.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative hemodynamics and outcomes of patients on metyrosine undergoing resection of pheochromocytoma or paraganglioma

Abstract: Large hemodynamic oscillations were present in our PCC/PGL patients treated with MET + PBZ. These patients had a wider range of intraoperative blood pressure variations than PBZ-only patients. No differences in postoperative comorbid outcomes were found between MET + PBZ and PBZ-only groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The majority of our patients were pretreated with α-adrenergic blockade, but despite that we still observed large hemodynamic oscillations during ablations. This is consistent with previous observations that preoperative adrenergic blockade cannot entirely eliminate intraoperative hemodynamic oscillations in these patients [ 13 , 15 , 16 ]. In our series, 1 patient was admitted to the ICU after ablation for treatment of severe hypertension despite the fact that he received comprehensive preoperative adrenergic blockade (Table 5 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The majority of our patients were pretreated with α-adrenergic blockade, but despite that we still observed large hemodynamic oscillations during ablations. This is consistent with previous observations that preoperative adrenergic blockade cannot entirely eliminate intraoperative hemodynamic oscillations in these patients [ 13 , 15 , 16 ]. In our series, 1 patient was admitted to the ICU after ablation for treatment of severe hypertension despite the fact that he received comprehensive preoperative adrenergic blockade (Table 5 ).…”
Section: Discussionsupporting
confidence: 93%
“…Exceptions to the use of blockade are nonsecretory parasympathetic-derived skull base and neck PPGLs [ 18 ]. The details of our protocol used before surgical resection have been previously reported [ 13 , 15 , 16 ]. Our practice for preablation preparation of patients with metastatic PPGL lesions includes administering the same adrenergic blocking agents that are used for the surgical resection of a primary PPGL [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that urine MNs have been reduced for at least 50% from baseline after the administration of metyrosine ( 45 , 46 ). Although Butz et al reported that patients treated with metyrosine and pheoxybenzamine had wider range of intraoperative blood pressure variations than phenoxybenzamine-only patients ( 47 ), it has been reported by most studies that the combination of metyrosine and α-AR antagonists lead to better blood pressure control, decreased intraoperative blood loss, and reduced volume replacement during operation compared with the classical method of monotherapy of α-AR blockade ( 45 , 46 , 48 , 49 ). In a case report of a patient with PPGL, the administration of metyrosine alone was unable to satisfactorily control intraoperative blood pressure ( 50 ), which was probably due to the incomplete depletion of CA stores no matter what dose used.…”
Section: Ca Synthesis Inhibitormentioning
confidence: 99%
“…This results in a reduction of circulating catecholamine levels by 50% to 80% (53). The initial oral dose is usually 250 mg 3 times a day, which may gradually be increased to a maximum daily dose of 4 g. In general, metyrosine is prescribed in combination with an α-adrenergic receptor blocker, in particular phenoxybenzamine [54][55][56]. A few case reports suggested that monotherapy with metyrosine is less effective (57,58).…”
Section: Alternatives To α-Adrenergic Receptor Blockersmentioning
confidence: 99%